Business Finance and Value-Added Evaluation of Pagar Alam Robusta Coffee (Coffea Canephora) Functional Product with the Addition of Crude Catechin Extract from Gambir (Uncaria gambir (Hunter) Roxb) (International Journal of Applied Research and Innovation, 2026)
This study evaluates the value added, operational cost dynamics, and ex-ante capital budgeting of full-wash Pagar Alam Robusta coffee enriched with a four percent crude catechin extract from gambier. Primary empirical processing parameters from field processing units were integrated into a enterprise simulation operating at 270 kilograms per cycle. Value-added transformation was determined using the Hayami method, while multi-year feasibility was evaluated over a five-year horizon discounted at four point seven five percent. Results show that the functional formulation yields a value-added margin of IDR 189,265 per kilogram, representing a value-added ratio of 52.57 percent. At full cycle capacity, the unit production cost of IDR 130,682 per kilogram and a cost-plus retail price of IDR 347,000 per kilogram generate an operational surplus of IDR 58,405,833 per batch. Discounted cash flow analyses indicate an ex-ante net present value of IDR 434,485,985.07, an internal rate of return of 51.80 percent, and a benefit-cost ratio of 1.031 against an initial outlay of IDR 250,650,000. Therefore, bio-fortifying Robusta coffee with natural catechins represents a financially feasible agro-industrial enterprise.